2000
DOI: 10.1046/j.1365-2311.2000.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of two macrolepidopteran assemblages on Salix nigra (Marsh) and Acer negundo L.: abundance, diversity, richness, and persistence of scarce species

Abstract: Summary 1. Most insect species occur at low abundance but a greater research effort has been devoted to so‐called outbreak species and little research is available on scarce (low abundance) species that are typical of most insect species. 2. Larval free‐feeding macrolepidoptera of two riparian trees Salix nigra (Marsh) (black willow) and Acer negundo L. (box elder) were sampled and sorted by species and abundance. 3. Data collected established that the majority of species in the assemblages in each tree specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 15 publications
4
23
0
2
Order By: Relevance
“…Our three studied parcels revealed a community of caterpillars with high species richness, low number, and low frequency on the host plant. These results confirmed the pattern found for tropical herbivore insects associated with host plants Barbosa et al 2000;Novotny and Basset 2000). The fact that an asymptotic curve was not reached may be a result of insufficient sampling, which is very common in systems of plant/herbivore insects (Lewinsohn et al 2005).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our three studied parcels revealed a community of caterpillars with high species richness, low number, and low frequency on the host plant. These results confirmed the pattern found for tropical herbivore insects associated with host plants Barbosa et al 2000;Novotny and Basset 2000). The fact that an asymptotic curve was not reached may be a result of insufficient sampling, which is very common in systems of plant/herbivore insects (Lewinsohn et al 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Immature Lepidoptera are the main defoliators of any natural or cultivated terrestrial ecosystem in temperate and tropical regions (Barbosa 1993). The Cerrado of Brasilia possesses a diverse array of lepidopterans.…”
Section: Introductionmentioning
confidence: 99%
“…En ambas localidades más del 80% de la abundancia fue explicada por sólo dos especies, mientras que la mayoría de las especies alcanzaron bajos niveles de abundancia dentro del ensamble. Al respecto, Barbosa et al (2000) indicaron que la dominancia de ensambles de herbívoros por parte de relativamente pocas especies puede ser una característica común para varios hábitats.…”
Section: Resultados Y Discusiónunclassified
“…and Fraxinus sp., and also among other tree genera in Finnish forests (Neuvonen, Niemelä 1981, 1983. In North America Barbosa et al (2000) compared caterpillar faunas from Salix nigra and Acer negundo and confirmed a high proportion of caterpillars were host species specific. However, argues that the degree to which species diversity found on any particular host tree varies due to random chance is unknown.…”
mentioning
confidence: 77%